Case Report: J-Shaped External Fixator for Treatment of Mayo Type II Olecranon Fractures – A Novel Surgical Technique and Report of Clinical Applications - Tian, Yue; Ge, Xin; Zou, Jiyang; Song, Fenglei; Cheong, John Chun tien chui wan; Ge, Changqing; Zhang, Weiguo; Li, Jie; Tian, Kang (Frontiers in Surgery, 2022)
Purpose We designed the J-shaped external fixator (J-EF) to provide minimally invasive, one-step surgical method for olecranon fractures. The aim of this study is to retrospectively review the method and the outcomes in 14 patients treated with J-EF fixation. Methods Biomechanical comparative study was performed for testing tensile properties of the J-EF using universal testing machine. Between January 2002 and December 2005, 14 patients (age range, 25-67 years) with Mayo type II olecranon fractures were treated using the external fixation technique. Follow-up was by standard measures (radiography, range of motion, and complications monitoring) and patient-reported outcome (Mayo Elbow Performance Score [MEPS] and Disabilities of the Arm, Shoulder and Hand [DASH] scores) at six months after surgery. Eight of the patients were reviewed at 15 years after the surgery. Results Results from biomechanical studies indicate the non-inferiority of J-EF to TBW in tensile properties. At time of release, the mean elbow flexion arc was 132.5° and mean forearm rotation arc was 173.6°. The mean DASH score was 14.1 points, and the mean MEPS was 93.9 points. Operative time and intraoperative blood loss were shorter by 41.3% and 64.6%, respectively, in J-EF patients than in a comparable group treated by TBW. All eight patients alive at 15 years after the surgery had maintained the original outcome. Conclusions External fixation using the J-EF appear to be a reliable, minimally invasive, and time-saving alternative treatment for Mayo type II olecranon fractures.